ENVIRONMENTAL FACTORS AND THEIR ROLE IN THE FORMATION OF PHYSIOLOGICAL INDICATORS OF YOUNG STUDENTS - Azimova Nozanin To’ymurodovna. (Western European Studies, 2024)
In a rapidly changing environment, primary school students find themselves in a zone of increased risk of environmental factors influencing their health. The article examines the impact of various components of the environment, such as air pollution, noise pollution, climate change and urbanization, on the physiological indicators of primary school children. The results of modern research are used to analyze the relationship between these factors and the state of children's health, statistical data confirming the importance of environmental adaptation in the school environment are presented.
Keywords: factors; ecology; changes; formation